Small Capital, Big Steps: The Evolution of Micro and Small Industries Under ISIC Amidst Economic Change - Ktut Silvanita Mangani; Lenny Lenny (Jurnal Riset Akuntansi, 2026)
This study examines the resilience and development of Micro and Small Industries (MSIs) in Indonesia between 2019 and 2023, emphasizing their contribution to the national economy during and after the COVID-19 pandemic. Using sectoral aggregate data obtained from the Central Statistics Agency and classified according to the International Standard Industrial Classification (ISIC), the study applies descriptive and trend analysis to evaluate changes in business performance. The findings reveal that although the number of MSIs declined during 2020 and 2021 due to the pandemic, the sector demonstrated a strong recovery in 2022 and 2023. The food manufacturing industry (ISIC 10) emerged as the leading contributor, recording substantial growth in both the number of enterprises and total revenue. The analysis also indicates that MSIs continue to rely primarily on internal capital, while the use of external financing has gradually increased to support business expansion. Consumer demand has shifted toward household markets, accompanied by wider adoption of direct-to-consumer strategies and digital marketing platforms, including social media and online marketplaces. Overall, the findings demonstrate the adaptability and resilience of Indonesian MSIs in responding to economic disruptions and evolving market conditions.